The happy artist? An empirical application of the work-preference model - Lasse Steiner; Lucian Schneider (University of Zurich, Department of Economics, 2011)
The artistic labor market is marked by several adversities, such as low wages, above-average unemployment, and constrained underemployment. Nevertheless, it attracts many young people. The number of students exceeds the available jobs by far. A potential explanation for this puzzle is that artistic work might result in exceptionally high job satisfaction, a conjecture that has been mentioned at various times in the literature. We conduct the first direct empirical investigation of artists' job satisfaction. The analysis is based on panel data from the German Socio-Economic Panel Survey (SOEP). Artists on average are found to be considerably more satisfied with their work than non-artists, a finding that corroborates the conjectures in the literature. Differences in income, working hours, and personality cannot account for the observed difference in job satisfaction. Partially, but not fully, the higher job satisfaction can be attributed to the higher self-employment rate among artists. Suggestive evidence is found that superior procedural characteristics of artistic work, such as increased variety and on-the-job learning, contribute to the difference in job satisfaction.
Keywords: Z10; J24; J28; J31; 330; job satisfaction; artists; work-preference; cultural economics; Künstlerische Berufe; Arbeitszufriedenheit; Berufswahl; Selbstständige; Schätzung; Deutschland